2019
DOI: 10.1002/ces2.10013
|View full text |Cite
|
Sign up to set email alerts
|

Porous alumina ceramics by gel casting: Effect of type of sacrificial template on the properties

Abstract: The effect of type of sacrificial template on the processing and properties of porous alumina ceramics was investigated. Two templates, (a) hollow pre‐expanded polymer spheres (Expancel) and (b) dense glassy carbon, were used to prepare porous alumina ceramics by gel casting. The results showed that the burnout of sacrificial expandable polymer microspheres from alumina ceramics was 10 times faster than glassy carbon without compromising the compressive strength. Moreover, the effect of the size of the porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This foamed body attains high strength by the combination of gel and foaming (Sepulveda 1997). The schematic representation of gel-casting process (Hooshmand et al 2019) is shown in Fig. 11.…”
Section: Gel Castingmentioning
confidence: 99%
“…This foamed body attains high strength by the combination of gel and foaming (Sepulveda 1997). The schematic representation of gel-casting process (Hooshmand et al 2019) is shown in Fig. 11.…”
Section: Gel Castingmentioning
confidence: 99%
“…Porous microspheres possess large surface areas and can be manufactured with large external and internal (usually interconnected) pores, to enable delivery of drugs, cells or other biologics. [34][35][36] There are various strategies for the production of porous bioactive glasses and/or ceramics, including the incorporation of a removable space holder (via sintering), [37] sol-gel, [38] gel-cast forming, [39] polymer foam replication, [40] solid-free form (3D printing), [41] and more recently flame spheroidization. [42] The single-stage, flame-process is a rapid, cost-effective and highly promising technique for large-scale production of porous glass and glassceramic microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 The manufacture of porous structures is dependent strongly on the type of material employed. For the case of glass and/or ceramic scaffolds, methods such as the incorporation of a removable space holder (via sintering), 6 polymer foam replication, 7 sol-gel, 8 gel-cast foaming, 9 or solid free-form (3D printing) approaches 10 are typically employed. However, these methods generally involve numerous processing steps which can be time-prolonged and laborious.…”
Section: Introductionmentioning
confidence: 99%